PKM2 uses control of HuR localization to regulate p27 and cell cycle progression in human glioblastoma cells. Issue 1 (2nd March 2016) - Mukherjee, Joydeep; Ohba, Shigeo; See, Wendy L.; Phillips, Joanna J.; Molinaro, Annette M.; Pieper, Russell O.
Abstract : The M2 isoform of pyruvate kinase (PK) is upregulated in most cancers including glioblastoma. Although PKM2 has been reported to use dual kinase activities to regulate cell growth, it also interacts with phosphotyrosine (pY)‐containing peptides independently of its kinase activity. The potential for PKM2 to use the binding of pY‐containing proteins to control tumor growth has not been fully examined. We here describe a novel mechanism by which PKM2 interacts in the nucleus with the RNA binding protein HuR to regulate HuR sub‐cellular localization, p27 levels, cell cycle progression and glioma cell growth. Suppression of PKM2 in U87, T98G and LN319 glioma cells resulted in increased p27 levels, defects in entry into mitosis, increased centrosome number, and decreased cell growth. These effects could be reversed by shRNA targeting p27. The increased levels of p27 in PKM2 knock‐down cells were caused by a loss of the nuclear interaction between PKM2 and HuR, and a subsequent cytoplasmic re‐distribution of HuR, which in turn led to increased cap‐independent p27 mRNA translation. Consistent with these results, the alterations in p27 mRNA translation, cell cycle progression and cell growth caused by PKM2 suppression could be reversed in vitro and in vivo by suppression of HuR or p27 levels, or by introduction of forms of PKM2 that could bind pY, regardless of their kinase activity. These results define a novel mechanism by which PKM2 regulates glioma cell growth, and also define a novel set of potential therapeutic targets along the PKM2–HuR–p27 pathway. Abstract : What's new? Pyruvate kinase M2 (PKM2) is overexpressed in many tumors, where it facilitates glycolysis and promotes tumor growth through interactions with phosphotyrosine (pY)‐containing peptides. Its exact contributions to tumor cell growth, however, are not fully understood. Here, PKM2 is shown to leverage its pY‐binding ability to interact in the nucleus with the RNA‐binding protein HuR, thereby promoting glioma cell growth. Disruption of the interaction resulted in cytoplasmic redistribution of HuR, increased cap‐independent p27 mRNA translation, and cell cycle arrest. The work defines a novel set of potential therapeutic targets along the PKM2–HuR–p27 pathway.